PENGARUH PROFITABILITAS, LEVERAGE, DAN NILAI PERUSAHAAN TERHADAP INCOME SMOOTHING DAN RETURN SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Oktyawati, Dianila; Agustia, Dian (JURNAL AKUNTANSI DAN AUDITING, 2014)
Income smoothing is an effort to reduce fluctuations of earnings by manipulating earnings so thatthe amount of profit a period is not too different from the amount of profit the previous period. Theaim of income smoothing is to improve perceptions of management’s performance and improvethe company’s image in the eyes of external parties. The existence of income smoothing gave animpact on the stock return. The aim of this paper was to study and to know the empirical evidenceabout the impact of profitability, leverage, and value of firm due to income smoothing and stockreturn. This study was as a basic research by using quantitative approach. Secondary data wasused in this study and it’s included the finance report and stock market of Manufacturing Companywhich was registered in Bursa Efek Indonesia (BEI) during the year of 2008-2010. Sample of this paper was 68 firms was gotten by purposive sampling method. This study used path analysis method. The result showed that profitability and leverage had significant and positive impact onincome smoothing. While the value of the company did not have a significant impact on incomesmoothing. Income smoothing had significant and negative impact on the stock return. This studyalso showed that profitability, leverage, and value of company did not have a significant impacton the stock return. Income smoothing as intervening variables did not give impact partiallybetween profitability, leverage and value of company to the stock return.